Developing mathematics video assisted by powtoon application in contextual learning approach. Issue 1 (February 2021) - Mujib; Mardiyah; Farida; Rachmadina, Destria; Pratiwi, Dona Dinda
Abstract: The purpose of this research and development was to develop an instructional media assisted by PowToon application in a contextual learning approach on statistical material for eighth-grade students of SMP Muhammadiyah 1 Kalianda and MTs Negeri 1 Bandar Lampung. The study was conducted to test the feasibility and attractiveness of the developed learning media. ADDIE model was used as the development model (Analyze, Design, Development, Implementation, and Evaluation). The developed media was categorized as feasible based on media and material expert validation. Sixty respondents on a small scale and large scale trials stated that the developed learning media was very interesting with the obtained percentage of 87%. It can be concluded that the developed media produced good results in its implementation.